Remote monitoring in patients with heart failure with cardiac implantable electronic devices: a systematic review and meta-analysis. Issue 2 (28th November 2022) - McGee, Michael J; Ray, Max; Brienesse, Stepehn C; Sritharan, Shanathan; Boyle, Andrew J; Jackson, Nicholas; Leitch, James W; Sverdlov, Aaron L
Abstract : Background: Remote monitoring (RM) of cardiac implantable electronic devices (CIEDs) is now the standard of care, but whether the demonstrated benefits of RM translate into improvements in heart failure (HF) management is controversial. This systematic review addresses the role of RM in patients with HF with a CIED. Methods and results: A systematic search of the literature for randomised clinical trials in patients with HF and a CIED assessing efficacy/effectiveness of RM was performed using MEDLINE, PubMed and Embase. Meta-analysis was performed on the effects of RM of CIEDs in patients with HF on mortality and readmissions. Effects on implantable cardiac defibrillator (ICD) therapy, healthcare costs and clinic presentations were also assessed. 607 articles were identified and refined to 10 studies with a total of 6579 patients. Implementation of RM was not uniform with substantial variation in methodology across the studies. There was no reduction in mortality or hospital readmission rates, while ICD therapy findings were inconsistent. There was a reduction in patient-associated healthcare costs and reduction in healthcare presentations. Conclusion: RM for patients with CIEDs and HF was not uniformly performed. As currently implemented, RM does not provide a benefit on overall mortality or the key metric of HF readmission. It does provide a reduction in healthcare costs and healthcare presentations. PROSPERO REGISTRATION NUMBER: CRD42019129270.